Making truth in early modern Catholicism - Badea, Andreea; Boute, Bruno; Cavarzere, Marco; Vanden Broecke, Steven, 1971- (Scientiae studies, 2021)
Scholarship has come to value the uncertainties haunting early modern knowledge cultures; indeed, the awareness of the fragility and plurality of knowledge is now offered as a key element of 'Baroque Science'. Yet early modern actors never questioned the possibility of certainty itself; including the notion that truth is out there, universal, and therefore situated at one remove from human manipulations. This book addresses the central question of how early modern actors managed not to succumb to postmodern relativism, amidst uncertainties and blatant disagreements about the nature of God, Man, and the Universe. An international and interdisciplinary team of experts in fields ranging from Astronomy to Business Administration to Theology investigate a number of practices that are central to maintaining and functionalizing the notion of absolute truth, the certainty that could be achieved about it, and of the credibility of a wide plethora of actors in differentiating fields of knowledge.